The Effect of Grammarly App as an Artificial Intelligence Media On The Students` Writing Ability in Recount Text for Grade Ten at Sma Negeri 5 Pematangsiantar - Simanjuntak, Gina Wijaya; Siahaan, Basar Lolo; Munthe, Melda Veby Ristella (Innovative: Journal Of Social Science Research, 2025)
This research aims to determine whether or not there is an effect of Grammarly Application media on students' writing ability in recount text in tenth grade students. This research used quantitative research methods and adopted a quasi-experimental design. The population of this research included all grade X students at SMA Negeri 5 Pematangsiantar with a total of 346 students. From this population, 36 students from each of the X-1 and X-2 classes were selected as research samples selected using a purposive sample approach. The assessment tools used were Pre-Test and Post-Test in writing. This study used Brown's standardized assessment for writing, which includes elements, focusing on grammar, vocabulary, and technicalities. The data analysis process involved the use of SPSS 30. This software facilitates several tests, including descriptive analysis, normality, Wilcoxon, homogeneity and Mann Whitney tests. From the findings, it was revealed that the Assymp. Sig (2-tailed) is < 0.001 < 0.005. Consequently, Ha is accepted while Ho is rejected. The skill of writing recount text among students in SMA negeri 5 Pematangsiantar was found to be highly influenced by the action of Grammarly application as artificial intelligence media.